Current Status of Market Mavens Research: A Literature Review - Alhamzah F. Abbas; Ahmad Jusoh; Adaviah Mas’od; Alaa Mahdi Sahi; Saleh F. A. Khatib (Emerging Science Journal, 2023)
Despite the growth of empirical evidence in this field, little review research exists that assesses the theoretical aspects, marketing drivers, and consequences of market mavens. In this study, therefore, a systematic literature review (SLR) was utilized to perform a thorough analysis of market maven literature, encompassing articles published over 23 years on the Scopus and Web of Science indexed journals. It was found that the social and psychological aspects had not been widely explored and remained the weakest pillar. The results highlight that the theory of planned behavior has been the most commonly applied theory in the literature, as it has been used in six studies. Moreover, there is a very limited understanding of the existing literature's psychological and motivational characteristics and their role in cyber-market mavenism. To the best of the authors’ knowledge, this is the first SLR that addresses market maven literature. This research offers a comprehensive study agenda that focuses on various critical areas that need more consideration, such as the cultural role of market mavens and the differentiation between the roles of market mavens and non-mavens in sharing information on social network sites. Scholars might also look at the influence of the generational difference between people and whether or not placing an age or gender limit on people is important in terms of the nature of social networks. Doi: 10.28991/ESJ-2023-07-01-019 Full Text: PDF